DESAIN DAN IMPLEMENTASI SOFTWARE AS SERVICE PADA PENGELOLAAN ABSENSI KEDISIPLINAN MAHASISWA POLITEKNIK NEGERI LAMPUNG - Fathoni, Halim; Kenali, Eko Win (Jurnal Informatika, 2014)
Cloud computing and the Internet is the latest generation in the world of informationÂ technology (IT). This technology allows an organization to save costs IT infrastructureÂ investments, in general, the organization that will use IT must build a data center thatÂ consists of multiple servers and build a whole needs supporters such as backup power,Â data backup and others are certainly in need of funds a little. With cloud computingÂ technology was submitted burden on providers including peraawatan costs. Based on theÂ type of service it, cloud computing is divided into three: SaaS (Software as a Service), PaaS (Platform as a Service), and IaaS (infrastruture as a Service) (Juan, 2012). SaaS isÂ an application that is intended to be used multiple users and invested in cloudÂ Infrastructure generally accessed through the Internet by using a browser (firefox, chrome,Â etc.). In the traditional way of software deployed by installing on a desktop computer andÂ its common one license for each computer. In the SaaS application can be used withoutÂ having to install on the computer (Juan, 2012). This research emphasizes on how to buildÂ software based on SaaS and itâs implementing POLINELA. Of these activities is expectedÂ to be dug deeper into the advantages and weaknesses of this technology. AttendanceÂ management discipline problems solved by the students try to build software based onÂ SaaS. With this technology officer can enter data from anywhere and at anytime, exceptÂ that students can check without having to make noise in the room departmentKeywords: Currently, Attendance, Lecturer Guardian, loud